Neural correlates of risk taking in violent criminal offenders characterized by emotional hypo- and hyper-reactivity - Prehn, Kristin; Schlagenhauf, Florian; Schulze, Lars; Berger, Christoph; Vohs, Knut; Fleischer, Monika; Hauenstein, Karlheinz; Keiper, Peter; Domes, Gregor; Herpertz, Sabine (Social neuroscience, 2013)
Recent approaches suggest that emotional reactivity can be used to differentiate between subgroups of individuals who are at risk for showing elevated levels of aggression and violence. In this study, we examined how emotion governs decision making within two subgroups of antisocial criminal offenders with either emotional hypo- or hyper-reactivity compared with healthy, noncriminal controls. Offenders were recruited from high-security forensic treatment facilities and penal institutions and underwent functional magnetic resonance imaging during a financial decision-making task. In this task, participants were required to choose between low-risk (bonds) and high-risk alternatives (stocks). Bonds were always the safe choice; stocks could win or lose, with a varying degree of uncertainty. We found that emotionally hypo-reactive offenders differed most from healthy controls by showing diminished neural activation in the rostral anterior cingulate cortex in response to uncertainty as well as decreased activity in the prefrontal cortex when trying to regulate their behavior accordingly (i.e., when consistently choosing “safe alternatives”). Hence, the data indicate that emotionally hypo-reactive offenders (with psychopathic traits) constitute a special subgroup within antisocial offenders characterized in particular by a limited capacity to emotionally represent uncertainty and to anticipate punishment.